PENGOLAHAN SEKAM PADI MENJADI BAHAN BAKAR ALTERNATIF MELALUI PROSES PIROLISIS LAMBAT - Suyitno Suyitno (JURNAL LITBANG PROVINSI JAWA TENGAH, 2009)
The aim of this research is to investigate the characteristic of alternative fuel obtained from slow pyrolysis of rice husk. The focus of this research is on the chemical characteristics, the physical characteristics and the performance of stove that using bio oil from slow pyrolysis of rice husk. The reseach was conducted experimentally in the laboratory. The construction of the slow pyrolysis reactor was an externally heating double pipe counter current flow heat exchanger. The rice husk was entered the reactor using a screw conveyor. The mass flow rate of rice husk was 5 kg/h. The reactor temperature at the wall near the flame source was controlled at 300, 400, and 500oC. The moisture contents of the rice husk were about 10,1% and 20,7%. There were three valuable products, i.e. the upper part of the bio oil, the bottom part of the bio oil, and the char. The upper part of the bio oil can be used for making bio briquette binder. The bottom part of the bio oil can be used as stove fuel after mixed with the ethanol. The char can be used as carbonization briquette. The substances in the bio oil was detected by GCMS (Gas Chromatography-Mass Spectrometry) and showed that more than 15 substances were detected. The bio oil was not stable in storage more than 7 days. The stove performance using blending of bio oil and ethanol was measured by water boiling method (WBT) and was calculated around 34,3%.